Study Habits and Examination Anxiety as Correlates of Students Attitudes Towards Examination Malpractices in Government Tertiary Institutions in Akwa State, Nigeria - Udoinyang, Nathan; Idiong, Onoitem Nkereuwem; George, Ibanga Utibe (International Journal of Applied Educational Research (IJAER), 2024)
This research looks at study habits and examination anxiety as correlates of students’ attitudes towards examination malpractice using government tertiary institutions in Akwa Ibom State as a case study. Survey methodology was employed to collect data from the population of students in tertiary institutions in Akwa Ibom State. A total of 328 people from 10 government tertiary institutions in Akwa Ibom State filled out the survey, The Taro Yamane formula was used to determine a sample size of 400. With a mean criterion of 3.0, the statistical tools of the Statistical Package for the Social Sciences (SPSS) were used to analyze the study's research topics. Reviewing the effects of study habits, causes of examination anxiety, and effects of students’ attitude towards examination malpractice will find that: poor time management, teaching strategies, peer pressure, threats from lectures, poor self-care and confidence, the quest for certificates, etc. all lead to examination malpractice in higher institutions in Akwa Ibom State. The study gave some recommendations and concluded that study habits, examination anxiety, and students’ attitudes have a joint influence on Examination malpractice therefore all hands must be on deck to make sure students in government higher institutions in Akwa Ibom State have a good study habits and attitude, and also eradicate any form of internal (within the educational system) examination anxiety from students so as to achieve knowledge and skills rather than a mere A4 certificate paper.